Does the invasive horse-chestnut leaf mining moth, Cameraria ohridella, affect the native beech leaf mining weevil, Orchestes fagi, through apparent competition? - Péré, Christelle; Bell, Robert; Turlings, Ted; Kenis, Marc (My University, 2011)
Apparent competition, through the action of shared natural enemies, is frequently suggested as a possible mechanism underlying the impact of invasive alien species on native species, but examples are rare, particularly in insects. A previous study showed that the beech leaf mining weevil, Orchestes fagi, was significantly less abundant close to horse-chestnut trees infested by the invasive horse-chestnut leaf mining moth, Cameraria ohridella, compared to control sites. Apparent competition through the sharing of natural enemies was proposed as a potential mechanism underlying this effect. To test the occurrence of apparent competition between the two leaf miner species, three observational studies and one experimental manipulation were carried out in Switzerland during 3 years. The total mortality, parasitism, predation and parasitoid diversity of larvae and pupae of O. fagi were compared between sites with and without horse-chestnut trees severely attacked by C. ohridella. Total mortality and predation rates of O. fagi were not significantly different between sites with and sites without C. ohridella. Despite a large overlap between the parasitoid complexes of the two leaf miners, parasitism of O. fagi was found to be positively influenced by the presence of horse-chestnuts infested by C. ohridella in only one of the four studies and only for 1 year. Similarly, parasitoid diversity was not higher near infested horse-chestnut trees compared to control sites. Thus, little evidence for apparent competition was found. Possible reasons, including possible insufficiencies in the experimental circumstances and design, are discussed.
Keywords: Apparent competition; Indirect interactions; Invasive alien insect; Leaf miner; Mortality rate; Native insect species; Parasitism; Parasitoid complex; Predation